Effects of thermal aging and absorbed hydrogen on fatigue crack growth behavior of welded C-Mn steels - Khattak, Muhammad Adil (2013)
The relatively high sulfur content in C-Mn steels and the hydrogen-rich operating environment renders high susceptibility of the steels to hydrogen-induced cracking, particularly in the welded steel plate connections. The objective of this study is to examine effects of thermal aging and absorbed hydrogen on fatigue crack growth behavior of the heat affected zone (HAZ) in welded Type A516 Gr 70 steels. Results showed that the fatigue crack growth rate behavior of HAZ displays a threshold growth stage followed by a power-law growth region until final fracture of the specimen. The threshold ?Kth for HAZ (13.2 MPavm) is lower than that for the base metal (15.5 MPavm). Both thermally aged and hydrogen-absorbed specimens showed a lower threshold ?Kth of 11.4 and 12.2 MPavm, respectively. In the high ?K region near final fracture of the specimen, the fracture mode is transgranular with the formation of dimples and micro-voids.